Principles of Voice & Data Communications - J. Bates Regis (Mc Graw Hill Irwin, 2007)
Principles of Voice and Data Communication is a technology book for the non-technical student, a comprehensive overview of the entire networking industry built on unrivaled real-world experience. With its helpful pedagogy, teaching support, and student-friendly tone, Principles of Voice and Data Communication gives students the foundation they need to enter, and succeed in, the technology and communications fields.